STRATEGI TOUR GUIDE DALAM MENINGKATKAN CITRA DESA WISATA LANTAN LOMBOK TENGAH MENGGUNAKAN METODE PUSH AND PULL FACTORS - Dimas Agung Pratama; Jumraidin, Jumraidin; H. Lalu Ratmaja (Bajang Institute, 2024)
This study aims to identify and analyze the driving and pulling factors that influence tourists' decisions in choosing lantan tourism villages as tourist destinations. The research used a qualitative approach. Data was collected through observation, interviews and documentation. The results of this study were obtained six factors that attract tourists to visit Lantan Tourism Village, namely, its natural beauty, enchanting waterfalls, adequate access, supporting facilities such as toilets, prayer rooms, trash cans and gazebos are available, there are products sold such as cascara tea, handicrafts from plastic waste, banana chips, taro chips and tourists can do activities other than enjoying the scenery such as cycling, soft tracking and participating in farming and gardening community activities. The strategies obtained are promotion, information, hospitality and service and cooperation with stakeholders